Analysis of quality control on cassava emping “Super Telur Bu Siti” in Bantul Karang Yogyakarta - Timur, Farradila Caesar Ratna; Fitriani, Aprilia (Universitas Ahmad Dahlan, 2024)
Cassava emping is a snack made from mashed cassava mixed with eggs, red chilies, green onions, and celery leaves. This research aims to analyze the quality control of cassava emping products and efforts to improve the production process of